THE IMPACT OF REMITTANCES ON ENTREPRENEURIAL BEHAVIOR IN THE PLACE OF ORIGIN - Khoury, Aline; Tong, Xiting (PEOPLE: International Journal of Social Sciences, 2021)
This research is mainly about remittances and the impact of remittances on building entrepreneurship. Remittances (money sent by migrants to their households in their place of origin) can play a significant role not only on household finances but also on the stimulus to local entrepreneurship in the places of origin. Still, the success of these entrepreneurial initiatives depends on the circumstances of different households and key socioeconomic conditions of the places in question. In this article, we aim to investigate which conditions of the households and the places of origin are likely to motivate the investment of remittances in entrepreneur activities. Our main methodology is the literature review, and here we examine various case studies addressing remittances investments in entrepreneurship, aiming to identify common key elements enabling and stimulating entrepreneurship in the cases examined. With this analysis, we aim to learn from the lessons of these case studies and then indicate ways to stimulate a sustainable investment of remittances in entrepreneurship in other contexts. Our main finding is several factors can contribute to setting up the entrepreneurship, namely, business environment; local policies; economic development in the host country; the mindset of remittance receivers and senders; the household’s income; the household’s culture, and kinship relations.